Effect of one session resistance exercise on skin sensibility in hypertensive and normotensive physically-active older woman. - Marilia Ceccato; Sandra Aires Ferreira; José Claudio Jambassi Filho; André Luiz Demantova Gurjão; Luiza Herminia Gallo; Alexandre Konig Garcia Prado; Sebastião Gobbi (Universidade Federal de Santa Catarina, 2011)
The aim of this study was to analyze the effect of a single session of resistance training on skin sensitivity in physically active, hypertensive and normotensive older women, as well as compare skin sensitivity in both groups. Thirty-two physically active women (mean age 65.8 } 5.1 years; weight, 69.5 } 13.7 kg; height, 1.60 } 0.1 m) participated in this study and were classified as hypertensive (n = 15) or normotensive (n = 17). All participants answered a clinical history questionnaire and the Modified Baecke Questionnaire for Older Adults. Before and after the resistance training session, the skin sensitivity of the dominant hand was assessed at seven anatomical sites on the dorsal and palmar surfaces by stimulation with a Semmes-Weinstein monofilament esthesiometer. The loads employed during the resistance training session were determined one week before the experimental protocol. The Wilcoxon test showed no statistically significant differences in the skin sensibility test before and after resistance training in either groups. However, the Mann-Whitney U revealed a statistically significant between-group difference in sensitivity at three sites before resistance training and at only site post-training. A single session of resistance training had no effect on the skin sensitivity of hypertensive and normotensive older women. However, hypertensive participants exhibited reduced skin sensibility at some anatomical sites as compared with normotensive women.